Manajemen Komunitas Belajar dalam Meningkatkan Motivasi Belajar Murid SMAN 1 Sukanagara - Yoseptry, Ricky; Astuti, Sri; Sumarwan, Usep; Ardiana, Ardiana; Nurrohmah, Siti; Wasliman, Eva Dianawati (JURNAL PENDIDIKAN DAN KEWIRAUSAHAAN, 2024)
This research discusses how Learning Community Management motivates student learning at SMAN 1 Sukanagara. This research aims to find out how the learning community is managed and to what extent it influences the competence of educators who will implement it in learning so that it will bring positive changes in the classroom which will increase student learning motivation. The type of research used is qualitative descriptive research using the case study method. Data collection techniques through interviews, questionnaires, observation, and document study. The research results show that learning communities that are carried out regularly provide positive changes to the competence of educators which have an impact on the student learning process. Active and fun learning will certainly influence student motivation to participate in learning. The learning community is also a place for developing personal character for educators to become more active, creative, and confident.